Benefits of early audiological intervention to inclusion of children with hearing impairment (2013)
It has been established by scholars that hearing loss can be detected from as early as prenatal stage of life. This is an aspect of early intervention services for children from age 0 - 3 years. Children whose hearing losses are attended to early enough are velop faster in terms of speech, hearing and language. This paper addressed the concept of early audiological intervention and inclusion of children with hearing impairment, benefits of early audiological intervention to children with hearing impairment, roles of audiologists and key components of early audiological intervention. Recommendations were made based on the submission of the authors.